Adventure time. The complete first season [videorecording (DVD)] - Ward, Pendleton, 1982- (Cartoon Network ; Distributed by Warner Home Video, 2012)
Cartoon Network's number one hit comedy show, Adventure Time is about the post-apocalyptic adventures of a boy named Finn, his friend Jake, a magic dog. Includes all 26 episodes of the first season.